2006
DOI: 10.1158/1535-7163.mct-06-0260
|View full text |Cite
|
Sign up to set email alerts
|

Anti-CD146 monoclonal antibody AA98 inhibits angiogenesis via suppression of nuclear factor-κB activation

Abstract: Our previous study showed that an anti-CD146 monoclonal antibody (mAb), AA98, which was raised against the vascular endothelial cells stimulated by a conditioned medium from hepatocarcinoma SMMC 7721 cells (SMMC 7721-CM), inhibited cell migration, angiogenesis, and tumor growth. However, the underlying mechanism was not elucidated. The objective of this study was to understand the mechanism by which mAb AA98 inhibits the endothelial cell migration and angiogenesis that is induced by SMMC 7721-CM. Using confoca… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

2
55
0
1

Year Published

2008
2008
2024
2024

Publication Types

Select...
9
1

Relationship

4
6

Authors

Journals

citations
Cited by 55 publications
(58 citation statements)
references
References 23 publications
2
55
0
1
Order By: Relevance
“…Likewise, a reciprocal regulation of MelCAM and Akt has been described in human melanoma (28). Finally, biochemical studies revealed that CD146 was required for the activation of p38/IKK/NFB signaling cascade and up-regulation of NFB downstream proangiogenic genes in response to tumor secretions (29). Examination of the angiomotin structure shows that it is lacking catalytic motifs and can therefore apparently not transduce signals by itself.…”
Section: Discussionmentioning
confidence: 99%
“…Likewise, a reciprocal regulation of MelCAM and Akt has been described in human melanoma (28). Finally, biochemical studies revealed that CD146 was required for the activation of p38/IKK/NFB signaling cascade and up-regulation of NFB downstream proangiogenic genes in response to tumor secretions (29). Examination of the angiomotin structure shows that it is lacking catalytic motifs and can therefore apparently not transduce signals by itself.…”
Section: Discussionmentioning
confidence: 99%
“…Anfosso et al (1998) found that CD146 crosslinking by a monoclonal antibody (mAb), named Sendo1, triggers the phosphorylation of FAK through association with Fyn. Moreover, our previous works revealed that CD146 mediates tumor secretion-induced p38/IkB kinase/nuclear factor-kB signaling cascade, which is pivotal in inducing endothelial cell activation, leading to tumor angiogenesis (Yan et al, 2003;Bu et al, 2006;Zheng et al, 2009). Nevertheless, fully understanding of CD146 signaling relies on the identifications of not only the ligand, but also intracellular binding partners and effectors.…”
Section: Introductionmentioning
confidence: 99%
“…(22) Further studies revealed that the mechanism of AA98-mediated anti-angiogenesis might involve its inhibition of CD146 dimerization, (23) MAPK phosphorylation, and NFB activation. (24) These evidences bring new insight into the function of CD146 in vascular and cancer biology.…”
mentioning
confidence: 98%